Influencing factors and enhancement strategies for vaccination behavior among Chinese residents: an empirical analysis based on a nationwide survey - Zhang, Meixia; Fang, Xiao; Wang, Mingshan; Pan, Ning; Wang, Hui; Liu, Zheng (Frontiers in Public Health, 2025)
BackgroundVaccination is a cornerstone of healthcare systems, and increasing vaccination coverage is crucial for achieving public health objectives globally. However, vaccine acceptance rates vary considerably across different regions worldwide. In China, understanding the determinants of vaccine acceptance is crucial for enhancing coverage and achieving public health goals.ObjectiveThis study examined the factors influencing vaccine acceptance among Chinese residents and proposes response strategies to enhance public vaccine acceptance, thereby contributing to public health development.MethodsBased on cross-sectional data from the 2023 Chinese Residents' Psychological and Behavioral Survey (PBICR), a questionnaire was administered to 30,011 participants using the eHEALS-SF Scale, Health Literacy Scale (HLS-SF4), Big Five Inventory-10 (BFI-10), General Risk Tendency Scale (GRiSP), and Media Motivation Scale. Univariate analysis was performed initially, followed by logistic regression for variables with a P ≤ 0.05, to examine the impact of demographic characteristics, health literacy, personality traits, and other factors on vaccination behavior.ResultsAmong Chinese residents, 57.23% reported receiving vaccinations. This included 4,555 (15.18%) who received the HPV vaccine, 12,103 (40.33%) the influenza vaccine (IFV), 2,450 (8.16%) the herpes zoster vaccine (HZV), and 9,172 (30.56%) the hepatitis vaccine. Univariate analysis identified 17 factors significantly associated with overall vaccination behavior (P < 0.05), including gender, age, education level, disease experience, health literacy, personality traits (e.g., openness and conscientiousness), and media influence. Logistic regression analysis revealed 11 associated factors: being female, aged 45–59 years, having a high education level, being a student, experiencing disease, residing in urban areas, earning high income, possessing high health literacy, exhibiting low openness, showing low risk tendency, and demonstrating high media motivation were positively associated with vaccination behavior (P < 0.05). Differences in the influencing factors between vaccines and the interaction of the vaccines are also found in the research.ConclusionThe acceptance of vaccines among Chinese residents was influenced by a combination of demographic characteristics, health perception, personality traits, and socioeconomic factors. To enhance vaccination coverage, it is essential to implement precise interventions, optimize information dissemination strategies, and provide personalized health services tailored to specific groups, such as those with low educational attainment, individuals residing in rural areas, and those with high openness personality traits.